THE URGENCY OF YELLOWISLAMIC BOOK LEARNING INNOVATION IN PESANTREN: A CASE STUDY OF THE MINIKOM DORMITORY AT PP MAMBAUL ULUM BATA-BATA - Sari Nusantara Putri; Roiq Masyhudi Hamid (Molang: Journal Of Islamic Education, 2024)
This study examines the effectiveness of educational management patterns in Minikom Pondok Pesantren Mambaul Ulum Bata-Bata in planning, program implementation, and supervision, the purpose of the study is to describe the implementation of educational management in the Minikom dormitory of Pondok Pesantren Mambaul Ulum Bata-Bata towards the effectiveness of student learning in the boarding school environment. The research method uses a qualitative approach by collecting primary data through interviews with the head of the management, the head of the dormitory, the teaching ustadz, and the students, as well as through direct observation. Secondary data includes documents such as dormitory profiles, organizational structures, and learning modules. Data analysis was carried out iteratively with data reduction techniques, data presentation in matrices or schemes, and conclusion drawing to understand more deeply about learning management in the final grade dormitory of the boarding school.The results showed that the pattern of education management at Pondok Pesantren Mambaul Ulum Bata-Bata involves a systematic planning process, comprehensive organization of activities, actuation to stimulate active participation of students, and careful supervision to ensure the achievement of goals according to plan. Management at the Minikom Dormitory involves planning that is prepared after the santri have graduated, intensive program implementation through various educational activities, and internal supervision by all administrators and teachers. This research emphasizes the importance of implementing effective education management to improve santri learning in boarding schools.